Pedagogical knowledge representation through concept mapping as a study and collaboration tool in teacher education - Koc, Mustafa (Australasian Journal of Educational Technology, 2012)
This study explored (a) pre-service teachers' perceptions of using concept mapping (CM) in one of their pedagogical courses, (b) the predictive power of such implementation in course achievement, and (c) the role of prior experience with CM, type of mapping, and gender on their perceptions and performances in CM and achievement. The subjects were 89 pre-service teachers majoring in technical education in Turkey. Each participant developed five concept maps and shared them with classmates. The data sources included assessments of concept maps, midterm exam scores, and student feedback questionnaires. Overall, participants had positive perceptions about CM. They indicated that CM helped them prepare for class lessons and examinations, understand complex issues, and reflect on their (mis)understandings. CM significantly predicted course achievement. Gender, prior experience with CM, and type of mapping were found to be insignificant factors in their perceptions and performances in CM and in the prediction of achievement. [Author abstract]